The prevalence of inherited metabolic disorders in Estonian population over 30 years: A significant increase during study period. Issue 6 (24th August 2022) - Tiivoja, Elis; Reinson, Karit; Muru, Kai; Rähn, Kristi; Muhu, Kristina; Mauring, Laura; Kahre, Tiina; Pajusalu, Sander; Õunap, Katrin
Abstract: Inherited metabolic disorders (IMD) are a group of hereditary diseases wherein the impairment of a biochemical pathway is intrinsic to the pathophysiology of the disease. Estonia's small population and nationwide digitalised healthcare system make it possible to perform an epidemiological study that covers the whole population. A study was performed in Tartu University Hospital, which is the only tertiary care unit in Estonia for diagnosing patients with IMD, to define the prevalence and live birth prevalence of IMDs and the effectiveness of new diagnostic methods on the diagnosis of IMD. During the retrospective study period from 1990 to 2017, 333 patients were diagnosed with IMD. Statistical analysis showed a significant increase in IMD diagnoses per year from 0.47 to 2.51 cases per 100 000 persons ( p  < 0.0001) during the study period. Live birth prevalence of IMD in Estonia was calculated to be 41.52 cases per 100 000 live births. The most frequently diagnosed IMD groups were disorders of amino acid metabolism, disorders of complex molecule degradation, mitochondrial disorders, and disorders of tetrapyrrole metabolism. Phenylketonuria was the most frequently diagnosed disorder of all IMD (21.6%). Our results correlated well with data from other developed countries and, along with high birth prevalence, add confidence in the effectiveness of our diagnostic yield. Implementation of new diagnostic methods during study period may largely account for the significant increase in the number of IMD diagnoses per year. We conclude that the implementation of new diagnostic methods continues to be important and contributes to better diagnosis of rare diseases.